Post-acute Transitional Journey: Caring for Orthopedic Surgery Patients in the United States - Stoicea, Nicoleta; Magal, Samarchitha; Kim, January K.; Bai, Michael; Rogers, Barbara; Bergese, Sergio Daniel (Frontiers in Medicine, 2018)
As the geriatric population in the United States continues to age, there will be an increased demand for total hip and total knee arthroplasties (THAs and TKAs). Older patients tend to have more comorbidities and poorer health, and will require post-acute care (PAC) following discharge. The most utilized PAC facilities following THA and TKA are skilled nursing facilities (SNFs), in-patient rehabilitation facilities (IRFs), and home with home health care (HHC). Coordination of care between hospitals and PACs, including the complete transfer of patient information, continues to be a challenge which impacts the quality of care provided by the PACs. The increased demand of hospital resources and PACs by the geriatric population necessitates an improvement in this transition of care process. This review aims to examine the transition of care process currently utilized for orthopedic surgery patients, and discuss methods for improvement. Employing these approaches will play a key role in improving patient outcomes, decreasing preventable hospital readmissions, and reducing mortality following THA and TKA. The extensive nature of this topic and the ramification of different types of healthcare systems in different countries were the determinant factors limiting our work.